Biological Behaviors of Guanidine‐Based Cationic Surfactants. Issue 3 (5th January 2014) - Song, Yongbo; Li, Qiuxiao; Li, Yunling; Zhi, Lifei
Abstract: The biological properties of novel guanidine‐based cationic surfactant including mono‐alkylguanidine (CnG), N, N, N ′‐dimethyl alkylguanidine (CnMG), dicephalic guanidine surfactant (CnGQ), heterogemini guanidine surfactant (diCnGQ) were investigated. Antimicrobial activity was determined via the inhibition of cell viability of the prepared compounds, which was measured against three strains of a representative group of microorganisms. The inhibitions of cell viability were basically about 90 % at the concentration of 25 mg L −1 to alkyl guanidium salts (CnG, CnMG), and higher than 95 % at a concentration of 10 mg L −1 to dicephalic guanidine surfactants (CnGQ) and heterogemini guanidine surfactants (diCnGQ). The interactions of bovine serum albumin (BSA) with guanidine surfactants were investigated by fluorescence technology and the effect on BSA conformation follow the order: diC12GQ > C12GQ > C12G > C12MG. At any particular concentration, the biological activity depends on the alkyl chain length to any series of guanidine‐based cationic surfactants.